PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA PEGAWAI KANTOR PEGADAIAN HARAPAN INDAH - Nurmaida, Ajeng Lulu; Khatimah, Husnul (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to examine the effect of job training and career development on employee job satisfaction at Pegadaian Harapan Indah Office. The research uses a quantitative approach with SPSS version 27 as the analysis tool. A total of 72 respondents participated in the study. The results show that job training has a significant influence on job satisfaction, with a significance value of 0.000 and a t-value of 5.434, indicating that better skills and job readiness increase employee satisfaction. Career development also shows a significant effect (significance 0.000; t-value 5.374), suggesting that growth opportunities play an important role in building motivation and loyalty. Both variables contribute positively to creating a more satisfying and productive work environment. The findings conclude that job training and career development significantly influence job satisfaction, highlighting their importance in human resource management practices to improve employee performance, engagement, and retention.Keywords: Job Training, Career Development, Employee Job Satisfication, Pegadaian, Human Resources